2009
DOI: 10.1007/s10509-008-9962-9
|View full text |Cite
|
Sign up to set email alerts
|

High Energy Density physics and Laboratory Planetary Science using intense heavy ion beams at FAIR facility at Darmstadt: the HEDgeHOB collaboration

Abstract: Field of High Energy Density (HED) physics is very important from the scientific as well as technological point of view and due to these reasons, it has been an area of very active research over the past many decades. Static as well as dynamic experimental configurations have been used to study this subject. Recently, a new approach that involves isochoric and uniform heating of matter by intense ion beams, has been proposed to generate HED sates in the laboratory. Extensive theoretical work has been carried o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Theoretical work has shown that an intense heavy ion beam can be efficiently employed to isentropically implode a sample material like hydrogen or water that will generate physical conditions which are expected to exist in the interiors of the giant planets in our solar systems as well as in exoplanets [9][10][11][12]. An experiment based on this scheme, named LAPLAS (Laboratory Planetary Sciences) has been proposed to study planetary physics at FAIR [9].…”
Section: Planetary Physics Research At Fairmentioning
confidence: 99%
“…Theoretical work has shown that an intense heavy ion beam can be efficiently employed to isentropically implode a sample material like hydrogen or water that will generate physical conditions which are expected to exist in the interiors of the giant planets in our solar systems as well as in exoplanets [9][10][11][12]. An experiment based on this scheme, named LAPLAS (Laboratory Planetary Sciences) has been proposed to study planetary physics at FAIR [9].…”
Section: Planetary Physics Research At Fairmentioning
confidence: 99%
“…Theoretical work on beam-target heating clearly demonstrated a special characteristic of ion beams, namely, "volume heating of matter" [12]- [28]. The ion beam deposits energy over an extended volume of the target, thereby generating exotic states of high pressure and high entropy in the sample, directly.…”
Section: Heavy Ion Heating and Expansion: The Hihex Schemementioning
confidence: 99%
“…This type of experiment is suitable for studying the problem of hydrogen metallization [17], [22][23][24][25], [28], [30][31][32], [35,36], [59][60][61][62][63], [64] or for creating physical conditions that are expected to exist in the interiors of the giant planets [65,66]. For this reason, this experiment is named LAPLAS (LAboratory PLAnetary Science).…”
Section: Laboratory Planateray Science: the Laplas Schemementioning
confidence: 99%
See 2 more Smart Citations